Assessing Photocatalytic Activity at the Nanoscale Using Integrated Optical and Electron Microscopy. (25th April 2016) - Debroye, Elke; Van Loon, Jordi; Gu, Xian; Franklin, Thomas; Hofkens, Johan; Janssen, Kris P. F.; Roeffaers, Maarten B. J.
Abstract : An integrated optical‐electron microscope is presented that enables the in situ study of dynamic processes on photoactive materials. Here, the deposition of metallic silver nanostructures at ZnO photocatalyst particles is monitored in real time under ambient conditions by means of scanning electron microscopy. Zinc oxide crystals are immobilized on an electron transparent silicon nitride window. By passing UV light through an opposing optically transparent window, the zinc oxide is illuminated resulting in the photocatalytic formation of silver nanostructures. Both windows are part of a specially designed liquid cell filled with a dilute aqueous silver nitrate solution. Using the presented system, different electron detectors are evaluated for their ability to provide detailed images despite the interference caused by the liquid surrounding the sample. Special care has to be taken since direct silver reduction from solution induced by the electron beam interferes with the photocatalytic process. Oxygen gas, produced during the photocatalytic reaction, is also shown to complicate the imaging of the dynamic nanoscale processes in the scanning electron microscope. Nevertheless, the integrated approach allows to directly establish structure–activity relationships and to unravel optically induced processes at nanostructured materials. Abstract : The photocatalytic deposition of silver nanoparticles on ZnO dumbbell crystals is dynamically followed in a novel integrated optical‐electron microscope. The reaction is studied in situ in a liquid sample holder with optically and electron beam transparent windows. Importantly, the impact of the electron beam on the chemical processes and materials properties needs to be taken into account.